Regional Policy Diversification to Maximize Blue Economy Potential in Kepulauan Riau Amid Indonesia-China Bilateral Cooperation - Andana, Fery; Saputra, Cantius Fransisco Wisnu Bayu (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2025)
Indonesia’s ambition to enhance its maritime economy has been reinforced by its bilateral cooperation with China through the Memorandum of Understanding (MoU) on Deepening Blue Economy Cooperation. This initiative presents a significant opportunity for maritime provinces like Kepulauan Riau, which possess vast marine resources yet remain underutilized. Despite having 96% of its territory covered by sea, the region's fisheries sector contributes only 1.72% to its Gross Regional Domestic Product (GRDP), revealing a substantial gap between potential and economic realization. This study aims to explore how regional policy diversification can optimize blue economy potential in Kepulauan Riau amid growing bilateral cooperation. A qualitative descriptive-analytical approach was employed, using secondary data from official statistics, government regulations, academic literature, and blue economy policy frameworks. The study identifies tourism, fisheries, renewable energy, maritime transport, and climate mitigation as key sectors for development. The findings suggest that integrating these sectors through tailored regional policies aligned with local characteristics can create a synergistic effect, amplifying the benefits of blue economy investments. Additionally, strategic policy alignment with national blue economy roadmaps and the inclusion of local stakeholders are crucial to ensure equitable and sustainable outcomes. In conclusion, the research highlights that regional diversification, guided by the principles of sustainability, inclusivity, and local relevance, is essential to transforming external cooperation into real and balanced economic growth for Kepulauan Riau. Such a strategy ensures that no community is left behind in the national pursuit of blue economy advancement.